Killing the Fathers of Värmland: Sacrificial Violence in Scandinavian Folklore. - Teitelbaum, Benjamin R. (Contagion: Journal of Violence, Mimesis & Culture, 2025)
The article focuses on how Scandinavian folklore, particularly the legend of Höök in Värmland, illustrates the Girardian theory of sacrificial violence and victim transformation. Topics include the mythologizing of communal violence through storytelling, the evolving narrative construction around scapegoats, and the cultural process of turning victims into revered figures.